Access to finance by small and medium scale enterprises from Savings and Loans Institutions in the Kumasi Metropolis - Aboagye, Robert (2011)
A Thesis submitted to the Department of Banking and Finance, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree Of Master in Business Administration.